The Moderating Role of Self Efficacy Toward Multiple Role Conflict and Job Performance - A. A. R. P. Sari, Raden; Haziroh, Awanis L.; Pramadanti, Amanda D.; Putra, Febrianur I. F. S. (Terbuka Journal of Economics and Business, 2021)
The focus of this study is to provide empirical evidence of the moderating effect of self efficacy on the relation of multiple role conflict on employee performance. In addition, this study also examines the effect of multiple role conflict and self-efficacy on job performance. One hundred female employees from four commercial/government banks were sampled in this study. Sampling using purposive sampling technique with the criteria have been working for more than one year, married and already have children. Data were collected through questionnaires and processed using Moderated Regression Analysis (MRA). The results showed that multiple role conflicts have a significant negative effect on job performance, self-efficacy has a significant positive effect on job performance. Meanwhile, self-efficacy is not able to weaken or strengthen the influence of multiple role conflicts on job performance, in other words, self-efficacy fails to become a moderating variable in this study.